A suitable mixed mode I/II test specimen for fracture toughness study of polyurethane foam with different cell densities. (February 2022) - Imani, D.M.; Aliha, M.R.M.; Linul, E.; Marsavina, L.
Highlights: Application of AENDB specimen for mixed mode I/II fracture toughness of PUR foam. Relationship between mixed mode fracture toughness envelope and foam density. Lower fracture toughness and fracture initiation angle compared to the other test samples. Prediction of test data with the Maximum tangential stress/strain criteria. Abstract: Rigid foam materials are among the low strength structural components that can be failed catastrophically under mechanical loads. Low fracture toughness is therefore a major failure mode in these materials and researchers try to find suitable testing methods for determining the fracture toughness of foam materials. In this research a suitable test specimen that is an edge notch disc bend specimen subjected to asymmetric three-point bending and called Asymmetric Edge Notch Disc Bend (AENDB) is proposed for conducting mixed mode I/II fracture experiments on polyurethane (PUR) foam with different cell densities. The geometry factors of the specimen that are required for determining the stress intensity factors were determined by means of the finite element analyses for different mode mixities. The mixed mode I/II fracture toughness envelope and fracture initiation angle were obtained for the (AENDB) specimen made of three foam densities ranging from 100 to 300 kg/m 3 . For example, K Ic and K IIc values were varied in the ranges 0.08–0.31 MPa.m 0.5 and 0.09–0.34 MPa.m 0.5, respectively. It was observed that the fracture toughness data are increased for all mode mixities by increasing the foam density. However, the mixed mode fracture curve and fracture initiation directions obtained from the AENDB specimen were lower than the corresponding curves of other mixed mode I/II test samples such as asymmetric semi-circular bend (ASCB) specimen. This can be attributed to the plane strain condition that is obtained at the mid-section of the AENDB specimen, since the crack front length in the AENDB specimen is significantly greater than the ASCB specimen. Finally, the experimental results obtained from the AENDB specimen were predicted using two fracture criterions. The results of this research indicate that the suggested AENDB specimen is a good candidate mixed mode I/II fracture configuration for investigating foam and other similar cellular materials.